CLINICAL EXPERIENCE OF LASER THERAPY USE IN RHINOSINUSITIS PATIENTS AFTER ENDOSCOPIC OPERATIONS - Ulugbek, Burkhanov; Nilyufar, Khushvakova (International Journal of Psychosocial Rehabilitation, 2020)
Chronic forms of rhinosinusitis are still an urgent problem in otorhinolaryngology and are among the most common diseases of ENT practice. The urgency of the problem of treating chronic forms of rhinosinusitis is caused not only by the frequency of this pathology, the severity of the course, the possibility of developing orbital and intracranial complications, and adverse outcomes. The development of often recurring forms of the disease, which, in some cases, become protracted, chronic, but also because the means and methods of treatment of this inflammatory process developed and used in practice are not always effective. The aim of this work is to assess the state of the cellular and humoral immunity system under the influence of low-intensity laser therapy in chronic forms of rhinosinusitis.